Metabolic Demand and Indirect Markers of Muscle Damage After Eccentric Cycling With Blood Flow Restriction. Issue 4 (1st October 2020) - Penailillo, Luis; Santander, Miguel; Zbinden-Foncea, Hermann; Jannas-Vela, Sebastian
ABSTRACT: Purpose : To compare the effects of a single bout of eccentric cycling (ECC) and eccentric cycling with blood flow restriction (ECCBFR ) on the changes in cardio-metabolic demand and indirect markers of muscle damage in healthy men. Method : Twenty-one young men (24.0 ± 3.2 y) were randomly allocated in two groups to perform a 30-min eccentric cycling bout with or without blood flow restriction. Oxygen consumption, heart rate, rate of perceived exertion and mean arterial blood pressure were monitored during cycling. Blood lactate was measured before and after cycling. Maximal voluntary isometric knee extensor strength and muscle damage were measured before, immediately after and 1–4 days after each eccentric cycling bout. Results : Oxygen consumption, heart rate, rate of perceived exertion and mean arterial blood pressure were similar between bouts. Blood lactate concentrations increased in both groups ( p < .01), with ECCBFR showing 60% greater blood lactate concentration than eccentric cycling ( p < .01). Maximal voluntary isometric knee extensor strength decreased 19-7% until 48 h and decreased 16-7% until 72 h after ECC and ECCBFR, respectively. Muscle soreness and pressure pain threshold remained elevated until 72 h after ECC and until 96 h after ECCBFR . Conclusion : These results show that ECCBFR induces similar cardiovascular stress, greater lactate production and longer time to recover than ECC alone. Thus, BFR can be safely implemented with eccentric cycling.